Petroleum Markets in Sub-Saharan Africa : Analysis and Assessment of 12 Countries - Kojima, Masami; Matthews, William; Sexsmith, Fred (World Bank, Washington, DC, 2014)
This regional study takes twelve oil-importing countries in Sub-Saharan Africa and asks the following two questions: does each stage in the supply chain, from import of crude oil or refined products to retail, seem to be efficiently run and are the efficiency gains passed on to end-users? And if not, what are the potential causes and possible means of remedying the problems? The study focuses on Burkina Faso, Cote d'Ivoire, Mali, Niger, and Senegal in West Africa and Botswana, Kenya, Madagascar, Malawi, South Africa, Tanzania, and Uganda in East and Southern Africa, covering a wide range of conditions that affect price levels, such as the market size, geography (whether landlocked or coastal), existence of domestic refineries, degree of sector liberalization including pricing, and level of economic development.